Evidence of Chlamydophila psittaci infection in captive Amazon parrots in Brazil - Raso, T. D.; Berchieri, A.; Pinto, A. A. (Amer Assoc Zoo Veterinarians, 2002)
The prevalence of Chlamydophila psittaci (formerly Chlamydia psittaci) infection was assessed in 95 apparently healthy, captive Amazon parrots from three breeder collections in southeastern and west-central Brazil. Cloacal swabs from 95 birds were tested for chlamydial antigen, which was detected by direct immunofluorescence (DIF), and serum samples from 44 of these birds were tested for antibodies to C. psittaci using an enzyme-linked immunosorbent assay. The prevalences of active infection as detected by DIF were 16.7%, 22.2%, and 56.1%, and seroprevalences were 100%, 87.5%, and 60% in flocks A, B, and C, respectively. We can therefore infer that C. psittaci may be widespread in captive parrot populations in Brazil.
Keywords: Chlamydiosis; Chlamydophila psittaci; Amazon parrots; direct immunofluorescence; dot-blot ELISA; Brazil